A Categorical 4-Year Child Neurology Residency: It's Time - Thompson-Stone, Robert; Gottlieb-Smith, Rachel; Rogers, Danny A.; Xixis, Kathryn; Pearson, Rachel; Pagano, Lindsay; Ream, Margie (Seminars in Neurology, 2025)
Child neurology training has undergone minimal change over the decades, despite a rapid growth in subspecialty knowledge, patient volumes, and complexity. The current 5-year structure, which was established due to necessary historical compromises between pediatrics and neurology, is increasingly misaligned with modern clinical practice and educational priorities. Most child neurologists no longer pursue dual pediatrics certification, and few provide neurologic care to adult patients. Meanwhile, the field has expanded significantly in complexity and volume, making it a large enough specialty to sustain an independent curriculum. We propose a streamlined 4-year categorical residency model that integrates relevant components of pediatrics and adult neurology while centering training around child neurology from the start. This model, which aligns better with structures seen in comparable specialties, prioritizes flexibility and increases the opportunities for longitudinal mentorship and professional development. Thoughtful planning and collaboration will be essential to surmount challenges during the transition, including changes in board certification and alterations to institutional funding. Modernizing child neurology training is essential to better prepare future specialists, support recruitment and resident development, and meet the evolving needs of children with neurologic disorders.
Keywords: child neurology; residency; graduate medicale ducation